Corporate Actions, Earning Volatility, And Exchange Rate Influence On Stock Price Stability - Agnes Soukotta; Muhammad Yusuf; Zarkasi Zarkasi; Efendi Efendi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The purpose of this study is to examine the factors that influence stock price stability as proxied by stock price volatility in the era of the Covid-19 pandemic. This study investigates empirically by utilizing the independent variable of corporate action, which is represented by dividend policy, earnings volatility, and exchange rate. Meanwhile, in this study, the dependent variable is stock price stability as measured by stock price volatility. The instance.The consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) were used in this study with the purposive sampling method from January to September 2022. A population of 163 companies and a sample of 53 companies were used. Secondary data is used in the analysis, and descriptive statistics, classic assumption tests, multiple regression analysis, and hypothesis testing are performed using SPSS 26.0 software. According to the findings of this study, variable earnings volatility and exchange rates have no effect on stock price stability as proxied by stock price volatility, while corporate action as proxied by dividend policy has an effect on stock price stability as proxied by stock price volatility.